Do cognitive training strategies improve motor and positive psychological skills development in soccer players? Insights from a systematic review - Slimani, M.; Bragazzi, N. L.; Tod, D.; Dellal, A.; Hue, O.; Cheour, F.; Chamari, K. (Journal of Sports Sciences, 2016)
Soccer players are required to have well-developed physical, technical and cognitive abilities. The present systematic review, adhering to Preferred Reporting Items for Systematic reviews and Meta-Analysis guidelines, examined the effects of cognitive training strategies on motor and positive psychological skills development in soccer performance and identified the potential moderators of the "cognitive training-soccer performance" relationship. Thirteen databases were systematically searched using keywords related to psychological or cognitive training in soccer players. The review is based on 18 studies, employing 584 soccer players aged 7-39 years. Cognitive strategies, particularly imagery, appear to improve sports performance in soccer players. Regarding imagery, the combination of two different types of cognitive imagery training (i.e., cognitive general and cognitive specific) has a positive influence on soccer performance during training, whereas motivational imagery (i.e., motivational general-arousal, motivational general-mastery and motivational specific) enhance competition performance. Younger soccer players employ cognitive general and cognitive specific imagery techniques to a greater extent than older soccer players. Combined cognitive training strategies were more beneficial than a single cognitive strategy relative to motor skills enhancement in elite (particularly midfielders) and amateur (i.e., when practising complex and specific soccer skills in precompetitive period) soccer players. In conclusion, it appears that there are differences in cognitive/psychological training interventions, and their efficacy, according to whether they are directed towards training or competition, and the age, standard and playing position of the players.